2011
DOI: 10.1111/j.1570-7458.2011.01181.x
|View full text |Cite
|
Sign up to set email alerts
|

Prolongation of the effective copulation period by fractionated‐dose irradiation in the sweet potato weevil, Cylas formicarius

Abstract: The sterile insect technique (SIT), based on the principles of population and behavioral ecology, is widely used to suppress or eradicate target pest insect populations. The effectiveness of SIT depends on the ability of released sterile males to mate with and inseminate wild females; however, the use of gamma radiation to induce sterility negatively affects both somatic cells as well as reproductive cells. Consequently, sterilization by irradiation drastically diminishes mating performance over time. It is we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Fractionation, however, allows the somatic cell to recover between doses [ 67 , 68 ] and is time consuming and increases the cost of the process. Kumano et al [ 69 ] developed a fractionated-dose irradiation method in C . formicarius in which a 200-Gy dose was divided into three 67-Gy doses to achieve complete sterility while maintain normal mating performance for 12 days, which is twice that resulting from a single dose.…”
Section: Discussionmentioning
confidence: 99%
“…Fractionation, however, allows the somatic cell to recover between doses [ 67 , 68 ] and is time consuming and increases the cost of the process. Kumano et al [ 69 ] developed a fractionated-dose irradiation method in C . formicarius in which a 200-Gy dose was divided into three 67-Gy doses to achieve complete sterility while maintain normal mating performance for 12 days, which is twice that resulting from a single dose.…”
Section: Discussionmentioning
confidence: 99%
“…C. formicarius eggs found in both treatments had a 99% chance of hatching, which triggered the development of larvae and growing inside the tuber. Because of the conventional insecticide used (lambdacyhalothrin) has no ovicidal ability (Stevenson et al, 2009;Kumano et al, 2011;Wang et al, 2014). Previous research reported that only conventional insecticides with active ingredients of phenylpyrazoles, ethiprole, organophosphates, and carbamate were toxic to Hymenoptera eggs.…”
Section: Number Of C Formicarius Eggs Found In Each Tubermentioning
confidence: 99%
“…The central importance of the releasing sterile male helps populations decrease, together with other methods, helps to make the location a pest free. Sterile males during mating with females will not result in progeny, which then produce in total decreased in population in the next generation [72]. For example, radiations cause adverse effects on somatic cells and lower insect viability, which affects fertility when there is an increase in absorption.…”
Section: Open Access Freely Available Onlinementioning
confidence: 99%